Analisis Pengaruh Corporate Social Responsibility, Corporate Governance, Kualitas Audit Dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2019-2021) - Bela Safira; Dwiyani Sudaryanti; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Financial reports are a benchmark for companies in carrying out their operational activities so that financial reports become a medium of communication between internal and external parties. Therefore, the financial reports produced by the company must have integrity, namely to fairly and fully disclose all of the company's financial activities. However, it is not uncommon for companies to manipulate financial statements to maintain a good image for the company. This study aims to obtain empirical evidence of the influence of corporate social responsibility, corporate governance, audit quality, and company size on the integrity of financial statements. The independent variables in this study are corporate social responsibility, corporate governance consisting of audit committees, institutional ownership, independent commissioners and managerial ownership, audit quality, and company size. While the dependent variable is the integrity of the financial statements. The sample for this research is a company listed on the IDX for the mining sector for 3 years from 2019 to 2021. The sample was obtained using a purposive sampling method. This type of research is a quantitative research using secondary data. The research data was analyzed using multiple linear regression analysis. The results of this study are corporate social responsibility, institutional ownership and managerial ownership have a significant positive effect on the integrity of financial statements. Company size has a significant negative effect on the integrity of financial statements. And the audit committee, independent commissioners and audit quality have no effect on the integrity of financial statements.Keywords : Corporate social responsibility, corporate governance, audit quality, size, integrity financial statement.